Oxidative stress induces monocyte‐to‐myofibroblast transdifferentiation through p38 in pancreatic ductal adenocarcinoma. Issue 2 (4th June 2020) - Huang, Xin; He, Chaobin; Hua, Xin; Kan, Anna; Mao, Yize; Sun, Shuxin; Duan, Fangting; Wang, Jun; Huang, Peng; Li, Shengping
Abstract: Background: Cancer‐associated fibroblasts (CAFs) are among the most prominent cells during the desmoplastic reaction in pancreatic ductal adenocarcinoma (PDAC). However, CAFs are heterogeneous and the precise origins are not fully elucidated. This study aimed to explore whether monocytes can transdifferentiate into fibroblasts in PDAC and evaluate the clinical significance of this event. Methods: CD14 + monocytes were freshly isolated from human peripheral blood. Immunofluorescence, reverse transcription‐quantitative PCR, western blot, flow cytometry and enzyme‐linked immunosorbent assay were used to detect the expression of αSMA, fibronectin, and other relevant molecules. In addition, latex beads with a mean particle size of 2.0 µm were used to assess the phagocytic capacity. Moreover, RNA sequencing (RNA‐seq) was performed to identify the differences induced by H2 O2 and the underlying mechanisms. Results: Immunofluorescence identified αSMA and fibroblast‐specific protein 1 expression by tumor‐associated macrophages in PDAC. The in vitro experiment revealed that oxidative stress (H2 O2 or radiation) induced monocyte‐to‐myofibroblast transdifferentiation (MMT), as identified by upregulated αSMA expression at both the RNA and protein levels. In addition, compared with freshly isolated monocytes, human monocyte‐derived macrophages increased fibronectin expression. RNA‐seq analysis identified p53 activation and other signatures accompanying this transdifferentiation; however, the p53 stabilizer nutlin‐3 induced αSMA expression through reactive oxygen species generation but not through the p53 transcription/mitochondria‐dependent pathway, whereas the p38 inhibitor SB203580 could partially inhibit αSMA expression. Finally, MMT produced a unique subset of CAFs with reduced phagocytic capacity that could promote the proliferation of pancreatic cancer cells. Conclusions: Oxidative stress in the tumor microenvironment could induce MMT in PDAC, thus inducing reactive stroma, modulating immunosuppression, and promoting tumor progression. Reducing oxidative stress may be a promising future therapeutic regimen. Abstract : Monocytes in human blood are recruited into PDAC tissues. Low intracellular levels of H2 O2 are important for fibronectin mRNA synthesis, protein expression and secretion. Oxidative stress can reduce the phagocytic capacity and simultaneously activate the p38‐MAPK signaling pathway, thus inducing αSMA mRNA and protein expression (monocyte‐to‐myofibroblast transdifferentiation). However, these cells do not express Col1. In addition, supernatant from these cells can stimulate pancreatic cancer cell (AsPC‐1) proliferation.